A reinvenção dos corpos femininos nas plataformas de camming: uma aproximação indisciplinar entre pornografia, arte e outras impossibilidades - Sanches, Thany (2022)
The corpus of this master's research the camming platforms Chaturbate and Camera Privê. Both present as actual forms of body control and body normatization; at the same time, activating intimacy experiences and production of subjectivities. This curious contradiction was one of the main reasons to develop this research. In addition to the bibliographic review based on the approach of the recent and brief scientific literature on the subject, three empirical procedures designed to expand the possibilities of experiences of experiences were tested: (1) transcreation of images published on such platforms by means of drawings and paintings, (2) mapping of bodies exposed on screens, conceived as articulations with the field of pornography studies; and (3)descriptions of what happens at the videochat rooms, according to some perfomative narratives. The main theoretical basis evolves from Greiner and Katz’s corpusmedia theory, which analyzes the theory of the body from its co-evolutionary processes with the environments, as well as the policies involved in these communication networks. In addition, authors that specifically analyze pornography, philosophy and technology (eg Williams, Foucault, Srinivasan, Moraes, Jones and Preciado) are discussed. The result is a pictorial-narrative experiment of subjectivities and emerging questions